Active instruments: on the use of university rankings in developing national systems of higher education. Issue 1 (2nd January 2017) - Lim, Miguel Antonio; Williams Øerberg, Jakob
ABSTRACT: This article questions the existing understanding of how global university rankings work to coordinate higher education policy. Rankings are often analyzed as accelerators of reform processes while their differences are overlooked. We suggest studying the particular encounters between rankers and national policy contexts as occasions for friction between policies, people, and practices across both national policy arenas and the ranking agencies. We draw on two multi-year field studies of India and Denmark to show how alignment between rankings and national reform agendas cannot be easily assumed. We present rankers in motion, policies in motion, and finally the complex nature of the ranking device that needs to be both a relevant and malleable policy instrument but also a fixed and legitimate standard. Policy-makers needed a reference point and the dynamic nature of rankings changed the policy processes themselves. We extend existing arguments about the role of rankings in policy-making by showing concretely how rankings are employed in and shape countries' quests for positioning in the global knowledge economy. Rankings demand new explorations of their production and open up a space for new understandings of the links between policy assemblages and wider processes of transformation.